2022
DOI: 10.3389/fonc.2022.855725
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Hodgkin Lymphoma: Including the Patient’s Voice

Abstract: Since the initial treatment with radiation therapy in the 1950s, the treatment of Hodgkin lymphoma has continued to evolve, balancing cure and toxicity. This approach has resulted in low rates of relapse and death and fewer short and late toxicities from the treatments used in pursuit of cure. To achieve this balance, the field has continued to progress into an exciting era where the advent of more targeted therapies such as brentuximab vedotin, immunotherapies such as PD-1 inhibitors, and chimeric antigen rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Currently, the US Food and Drug Administration and European Medicines Agency, recommend PROs as a prioritized treatment outcome ( 26 , 27 ). Indeed, the added value of including PROs in clinical trials of HL patients has previously been reported ( 28 30 ). Data derived from PRO assessment can provide the patient-level impact of regimens on event-free survival, overall survival, and tolerability of the acute as well as the long-term effects of treatment.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Currently, the US Food and Drug Administration and European Medicines Agency, recommend PROs as a prioritized treatment outcome ( 26 , 27 ). Indeed, the added value of including PROs in clinical trials of HL patients has previously been reported ( 28 30 ). Data derived from PRO assessment can provide the patient-level impact of regimens on event-free survival, overall survival, and tolerability of the acute as well as the long-term effects of treatment.…”
Section: Introductionmentioning
confidence: 95%
“…It is also important to note that improvement in QoL is included in the European Society of Medical Oncology Magnitude of Clinical Benefit Scale to determine the “value” of novel therapeutic options in cancer ( 31 33 ). Several systematic reviews on the use of PROs in clinical trials in the HL setting have previously been published ( 29 , 30 , 34 ). However, for trials involving HL patients, it still is unclear as to which PRO instruments are used, frequency of their use, and whether their results are consistently reported.…”
Section: Introductionmentioning
confidence: 99%